Implementation of Economic Scale for Contractors Grade 5 to Grade 7 During Covid-19 Pandemic - Roslan, Nur Izzati Nabilla; Mohamad Zulhairi, Norhazuren Ivy Nabila; Azhar, Aina Ilyana; Ahmad, Nor Farah Atiqah (Multidisciplinary Applied Research and Innovation, 2022)
Construction is one of the main sectors that contribute to the economy for Malaysia. Individuals who are directly involved with the construction industry is the contractor where the contractor was classified according to their performance and therefore, economic scale for each grade of contractor should be managed well. Movement control order (MCO) in Malaysia was implemented nationwide in early 2020 due to Covid-19 pandemic outbreak caused concern among the community as well as the contractors. Hence, the aim of this study is to address the main economic factor among contractors regarding this issue. Which later, analyse the influence of the Covid-19 pandemic on economic scale factors. The contractor from grade5 (G5) to grade7 (G7) in Kuantan, Pahang was selected for this study sample. The interviews and responds from contractors were collected by using personal interviews. Both qualitative and quantitative method were used to analyze the data in this study. The analysis shows that 84% of respondents are affected during Covid-19 pandemic and experienced project loss problems. The contractor’s effort in avoiding to become a dormant contractor are identified. It can be concluded that, the longer this Covid-19 problem is remained unsolved, the worse the economic problems of the country and society.